TINJAUAN PELAKSANAAN ASURANSI KECELAKAAN PENUMPANG DI PERUSAHAAN PENERBANGAN, (TINJAUAN UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN ) - Herlinus Patandean .P (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTThis study aims to determine any losses which are the responsibility of the insurer to domestic passengers, as well as to determine what factors are the obstacles in the realization of the responsibility of insurance against domestic flight passengers and how solutions address the problem tersebut.dan data collection techniques with interviews and studies dokumen.Berdasrkan research obtained result that the losses were the responsibility of the airlines and airline passengers are insured against death or injury of passengers, lost or damaged baggage and delays pesawat.Dalam passenger death or injury of passengers the carrier and the insurance reimburse besar.Kurang specific loss provisions regarding flight delays so that passengers who feel disadvantaged Because of not knowing the provisions regarding flight delays. The existence of the above, the need for clear provisions regarding flight delays.